The Influence of Optimum Water Content (Wopt) and Maximum Dry Density (γd) on Laboratory CBR Values at Grand Madinah Regency Housing, Balai Gurun Koto Nan Gadang, Payakumbuh City - Rivaldi Harianto; Hanifah Asnur; Sutria Desman (Fakultas Teknik Sipil dan Perencanaan, 2025)
Soil is a fundamental element in road construction, serving as the subgrade layer that supports vehicular loads, therefore, its charateristics particularly moisture content and soil compaction significantly affect bearing capacity, this study aims to analyze the effect of optimum moisture content and maximum dry density on the California Bearing Ratio (CBR) value obtained from laboratory test on soil from Grand Madinah Regency Housing area, Balai Gurun Koto Nan Gadang, Payakumbuh City. The theoretical foundation includes the concept of soil compaction based on the Standard Proctor Test and the CBR test as an indicator of subrage strength in pavement design. The research employed a quantitative experimental method, with soil samples collected directly from the field and tested at the Laboratory of Sekolah Tinggi Teknologi Payakumbuh using 10, 25, and 56 blows of compaction to analyze the relationship between moisture content, dry density, and CBR value. The results showed that the optimum moisture content was 38,08% and the maximum dry density was 0,73 gr/cm3. The laboratory CBR values obtained were 0,67%, 0,70%, and 0,72%, with a design CBR value of 0,69%. According to the CBR classification, the soil is categorized as very poor subrgrade, indicating that it is unsuitable as a subgrade layer without stabilization. In conclusion, an increase in moisture content reduces both density and CBR value, while optimal compaction significantly enhances the soil’s bearing capacity.